The Influence of Working Capital Management and ROE (Return On Equity) on Financial Performance at Letter Karya Timur Malang - Yohana Bernadita Hingi Purek; Agus Dwi Sasono; Moh. Askiyanto; Nur Ida Iriani (International Journal of Management and Business, 2026)
The aim of this study is to determine the effect of working capital management and return on equity (ROE) on financial performance at Letter Karya Timur Malang, both partially and simultaneously. Types of Quantitative Research. The data used is secondary data, in the form of financial statements in 2018-2024. Data analysis uses multiple linear regression analysis. Hypothesis testing using the T (partial) test and F test (simultaneous). Multiple linear regression results obtained by the two independent variables have a positive regression coefficient value and the coefficient of R Square's coefficient of 0.813 (contribution of the independent variable to the dependent variable of 81.3%). The results of testing the t (partial) test hypothesis found the two independent variables have a tcount > ttable value, with a significant <0.05; And the results of the F (Simultaneous) hypothesis testing obtained the Fcount > Ftable value, with significant <0.05. So it was concluded that working capital and return on equity (ROE) had a significant effect on financial performance at Letter Karya Timur Malang, both partially and simultaneously. Letter Karya management of East Malang is advised to increase the efficiency of working capital utilization and encourage profitability through cost management, increased profit margin, and optimizing income to support more optimal financial performance.